tert-Butyl 2-{[2,8-bis(trifluoromethyl)-quinolin-4-yl](hydroxy)methyl}-piperidi ne-1-carboxylate - Goncalves, R.S.B.; de Souza, M.V.N.; Wardell, J.L.; Wardell, S.M.S.V.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
The title molecule, C22H24F6N2O3, adopts a folded conformation whereby the carboxylate residue lies over the quinolinyl residue, with the dihedral angle between the carbamate and quinoline planes being 41.64 (7)degrees. Helical supramolecular C(7) chains sustained by O-H center dot center dot center dot O hydrogen bonds propagating along the a-axis direction feature in the crystal packing. The F atoms of one of the CF3 groups are disordered over two orientations; the major component has a site occupancy of 0.824 (7).